Immigrants and welfare programmes: exploring the interactions between immigrant characteristics, immigrant welfare dependence and welfare policy - Barrett, Alan; McCarthy, Yvonne (Dublin, 2008)
"The primary purpose of this paper is to provide a review of the papers within the economics literature that have examined the questions of immigrant welfare use and the responsiveness of immigrants to the incentives created by welfare systems. While our focus is largely on papers looking at the European case, we also draw on studies from the United States, in particular on issues where the European literature is thin. One set of papers asks whether immigrants who are more likely to use welfare are attracted to more generous welfare states. The results from these papers are not clear-cut. Another set of papers asks if immigrants use welfare more intensively than natives and if they assimilate out of or into welfare participation. In most cases, the unadjusted data shows higher use of welfare by immigrants although for some countries, for example Germany, this difference can be explained by differences in characteristics. Yet another set of papers finds that the rate of welfare use by existing migrants can influence the welfare use of newly arrived co-nationals. We illustrate some of these issues by looking at immigrant welfare use in Ireland and the UK. Immigrants in the UK appear to use welfare more intensively than natives but the opposite appears to be the case in Ireland."